2024
DOI: 10.1109/tit.2023.3286452
|View full text |Cite
|
Sign up to set email alerts
|

Reed–Muller Codes on BMS Channels Achieve Vanishing Bit-Error Probability for all Rates Below Capacity

Abstract: This paper considers the performance of Reed-Muller (RM) codes transmitted over binary memoryless symmetric (BMS) channels under bitwise maximum-a-posteriori (bit-MAP) decoding. Its main result is that, for a fixed BMS channel, the family of binary RM codes can achieve a vanishing biterror probability at rates approaching the channel capacity. This partially resolves a long-standing open problem that connects information theory and error-correcting codes. In contrast with the earlier result for the binary eras… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 60 publications
(162 reference statements)
0
0
0
Order By: Relevance
“…For this reason, when Arikan showed that polar codes achieve capacity over the BSC, Reed-Muller codes received renewed attention from the coding theory community. A long and fruitful line of work [4,38,6,25,1,47,50] has recently culminated in Abbe and Sandon showing that Reed-Muller codes achieve capacity over all BMS channels [2].…”
Section: List Decoding Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…For this reason, when Arikan showed that polar codes achieve capacity over the BSC, Reed-Muller codes received renewed attention from the coding theory community. A long and fruitful line of work [4,38,6,25,1,47,50] has recently culminated in Abbe and Sandon showing that Reed-Muller codes achieve capacity over all BMS channels [2].…”
Section: List Decoding Resultsmentioning
confidence: 99%
“…An important open question is thus whether general doubly transitive codes achieve capacity over all BMS channels under block-MAP decoding, or whether one really needs the additional symmetry that Reed-Muller codes possess. Some of the key techniques used in [47] and [2] are very much tailored to Reed-Muller codes, or at least to codes consisting of evaluations of polynomials over F N 2 ; in order to prove the same results for arbitrary doubly transitive codes, it may be necessary to develop a more general framework.…”
Section: List Decoding Resultsmentioning
confidence: 99%
See 1 more Smart Citation